Effects of yoga on sleep quality, fatigue and physical activity levels in patients with multiple sclerosis: A randomized controlled trial - Ozturk, Dilara; Turan, Gulcan Bahcecioglu (Elsevier Science Inc, 2026)
Introduction: Yoga may support symptom management in individuals with Multiple Sclerosis (MS) by improving sleep, reducing fatigue, and promoting physical activity. This study examined the effects of a six-week yoga program on sleep quality, fatigue, and physical activity levels in patients with MS. Methods: This randomized controlled trial included 60 patients with MS (30 intervention, 30 control). The intervention group completed 12 yoga sessions over six weeks, while the control group received no intervention. Sleep quality, fatigue, and physical activity were assessed using the Pittsburgh sleep quality index (PSQI), Fatigue severity scale (FSS), and international physical activity questionnaire-short form (IPAQ-SF). Results: Compared with the control group, the intervention group showed substantial improvements in sleep quality (mean difference-6.14, 95% CI-7.79 to-4.49). Fatigue severity was lower in the yoga group after the intervention (mean difference-1.48, 95% CI-2.44 to-0.52). Physical activity levels increased markedly in the intervention group (mean difference +1857.92 met-min/week, 95% CI 1355.7 to 2360.1). No adverse effects related to the yoga intervention were reported. Conclusion: A six-week yoga program improved sleep quality, reduced fatigue, and significantly increased physical activity levels in individuals with MS. Yoga may be considered a beneficial complementary approach in the care and symptom management of patients with MS.
Keywords: Nursing; Multiple Sclerosis; Sleep quality; Yoga; Fatigue; Physical activity